Postoperative pain and influencing factors after prophylactic extraction of impacted mandibular third molars: a multicenter prospective cohort study - Zhiwei Cao; Chengzhi Zhao; Renyi Wang; Qianxing Du; Kun Zhang; Jihong Zhao; Yang Xue; Bing Han; Jiuyan Jiang; Liwei Hu; Xuejuan Liao; Jian Pan (BMC Oral Health)
Abstract Objective This study aims to investigate factors influencing postoperative pain after prophylactic third molar extraction to provide evidence-based recommendations for clinical practice. Methods This study enrolled 804 patients undergoing prophylactic third molar extraction. Factors potentially influencing postoperative pain were meticulously documented, including patient demographics information, tooth impaction information, surgical procedure details information, and postoperative medication regimens information. Postoperative pain was assessed using the Visual Analog Scale (VAS) at 1, 3, 7, and 30 days, while postoperative infection was documented at the same intervals. Multiple linear regression and logistic regression analyses were performed to identify potential determinants of postoperative pain. Results Postoperative pain generally decreased over time (1d, 3d, 7d, 30d). A lower BMI and male gender were associated with lower early postoperative VAS scores (1d, 3d), while increased age and the use of filling materials were linked to higher early and intermediate postoperative VAS scores (1d, 3d, 7d). The application of glucocorticoids was associated with increased intermediate and late postoperative VAS scores (7d, 30d). The use of postoperative antibiotics did not affect the incidence of postoperative infections. Conclusion Results indicated that protective factors for postoperative pain following prophylactic third molar extraction include male, having a lower BMI, and the use of a trapezoidal flap. Risk factors include increasing age, longer surgery duration, the use of filling materials, and the use of glucocorticoids.